Digital Project Based Learning in Islamic Religious Education Using Canva on Halal and Haram Topics for Sixth-Grade Students at SD Alam Pacitan - Kristadi Tulistianto; Mohammad Khusnul Hamdani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the implementation of digital project-based Islamic Religious Education (IRE) learning using the Canva application on the topic of halal and haram for sixth-grade students at SD Alam Pacitan and to analyze its effectiveness in enhancing students' conceptual understanding and engagement during the learning process. Islamic Religious Education is commonly delivered through conventional lecture-based methods, resulting in limited student interest and passive classroom participation. Therefore, instructional innovation is needed to foster active learning, one of which is the implementation of the Project-Based Learning (PjBL) model supported by the Canva application. This study employed a descriptive qualitative approach. Data were collected through classroom observations, questionnaires, and documentation and were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that digital project-based Islamic Religious Education learning using Canva is reasonably effective in improving students' understanding and engagement throughout the learning process. The use of Canva as a learning medium also enhances students' digital literacy and technological skills. However, several challenges were identified, including reduced student focus and discipline during project activities, as well as unstable internet connectivity, which may hinder the effectiveness of technology-supported learning.